Resilience at the Transition to Agriculture: The Long-Term Landscape and Resource Development at the Aceramic Neolithic Tell Site of Chogha Golan (Iran). (6th August 2015) - Riehl, S.; Asouti, E.; Karakaya, D.; Starkovich, B. M.; Zeidi, M.; Conard, N. J.
Abstract : The evidence for the slow development from gathering and cultivation of wild species to the use of domesticates in the Near East, deriving from a number of Epipalaeolithic and aceramic Neolithic sites with short occupational stratigraphies, cannot explain the reasons for the protracted development of agriculture in the Fertile Crescent. The botanical and faunal remains from the long stratigraphic sequence of Chogha Golan, indicate local changes in environmental conditions and subsistence practices that characterize a site-specific pathway into emerging agriculture. Our multidisciplinary approach demonstrates a long-term subsistence strategy of several hundred years on wild cereals and pulses as well as on hunting a variety of faunal species that were based on relatively favorable and stable environmental conditions. Fluctuations in the availability of resources after around 10.200 cal BP may have been caused by small-scale climatic fluctuations. The temporary depletion of resources was managed through a shift to other species which required minor technological changes to make these resources accessible and by intensification of barley cultivation which approached its domestication. After roughly 200 years, emmer domestication is apparent, accompanied by higher contribution of cattle in the diet, suggesting long-term intensification of resource management.